Credit card industry : banks' marketing strategies vs consumers' preferences. - Fong, Clara Lyn. (2008)
The purpose of this study is to analyse how banks in Singapore market their credit cards and whether their marketing strategies match consumers' preferences. The framework for the analysis is based on the four Ps of the marketing mix -- product, price, place and promotion. A consumer survey was carried out and an interview with HongkongBank was conducted during the study. Findings indicate that banks in Singapore generally focus on the product and promotion aspects of credit card marketing.